THE METHODOLOGICAL STEPS EMPLOYED BY SA’ĪD AL-MARRĪ IN IDENTIFYING THE ‘ILLAH IN AL-HADĪTH AL-GHARĪB - Khoirunisa, Dinar Hanin; Firdaus, Mohamad Anang (LP2M Ma'had Aly Hasyim Asy'ari Pesantren Tebuireng, 2024)
This article discusses the method used by Sa'īd Muhammad Hamad al-Marrī in analyzing the causes of the ‘illah al-ḥadīth al-gharīb bi al-ḥadīth al-mashhūr (the criticism of a rare hadith based on a famous hadith) by some ulama who are experts in the criticism of hadith. The article aims to answer two main questions: what is the meaning of ‘illah al-ḥadīth al-gharīb bi al-ḥadīth al-mashhūr and what is Shaykh Sa'īd al-Marrī’s methodological approach in identifying the ‘illah in al-ḥadīth al-gharīb based on the existence of al-ḥadīth al-mashhūr. This article is written using a qualitative literature review method, with the book ‘Illah al-Ḥadīth al-Gharīb bi al-Ḥadīth al-Mashhūr by Shaykh Sa'īd al-Marrī as the main reference. The research sources include Sa'īd al-Marrī's work and other relevant secondary references related to the topic. The article finds that the method used by Sa'īd al-Marrī is the tanṣīṣ method, which involves two aspects of research: the sanad (chain of narrators) and the matn (content) of the hadith. The methodological steps are as follows: For the ‘illah in the sanad of the hadith: first, mentioning one version of the matn of the hadith. Second, mentioning the narration of the hadith from both the famous and the rare chains. Third, analyzing the 'illah in both chains of the hadith using the tanṣīṣ method. Fourth, drawing conclusions. This article is expected to help readers understand the method employed by Sa'īd al-Marrī as a contemporary scholar of hadith in analyzing the presence of ‘illah. [Artikel ini berfokus pada pembahasan metode yang digunakan oleh Sa'īd Muhammad Hamad al-Marrī dalam menganalisis penyebab ‘illah al-ḥadīṣ al-garīb bi al-ḥadīṣ al-masyhūr oleh beberapa ulama yang ahli dalam kritik hadis. Artikel ini bertujuan untuk menjawab dua pertanyaan utama: apa makna dari ‘illah al-ḥadīṣ al-garīb bi al-ḥadīṣ al-masyhūr dan bagaimana pendekatan metodologis yang digunakan oleh Syaikh Sa'īd al-Marrī dalam mengidentifikasi ‘illah dalam al-ḥadīṣ al-garīb berdasarkan keberadaan al-ḥadīṣ al-masyhūr. Artikel ini ditulis menggunakan metode tinjauan pustaka kualitatif, dengan buku ‘Illah al-Ḥadīṣ al-Garīb bi al-Ḥadīṣ al-Masyhūr oleh Syaikh Sa'īd al-Marrī sebagai referensi utama. Sumber penelitian meliputi karya Sa'īd al-Marrī dan referensi sekunder relevan lainnya yang berkaitan dengan topik tersebut. Artikel ini menemukan bahwa metode yang digunakan oleh Sa'īd al-Marrī adalah metode tanṣīṣ, yang melibatkan dua aspek penelitian: sanad (rantai periwayat) dan matn (isi) hadis. Langkah-langkah metodologisnya adalah sebagai berikut: Untuk ‘illah dalam sanad hadits: pertama, menyebutkan satu versi matan hadits. Kedua, menyebutkan riwayat hadis dari rantai yang masyhur dan yang tidak masyhur. Ketiga, menganalisis 'illah dalam kedua rantai hadis menggunakan metode tanṣīṣ. Keempat, menarik kesimpulan. Artikel ini diharapkan dapat membantu pembaca memahami metode yang digunakan oleh Sa'īd al-Marrī sebagai seorang ulama hadis kontemporer dalam menganalisis keberadaan ‘illah.]